A Dynamic Spatial Weight Matrix and Localized Space–Time Autoregressive Integrated Moving Average for Network Modeling. Issue 1 (January 2014) - Cheng, Tao; Wang, Jiaqiu; Haworth, James; Heydecker, Benjamin; Chow, Andy
<x xml:space="preserve">Abstract</x> Various statistical model specifications for describing spatiotemporal processes have been proposed over the years, including the space–time autoregressive integrated moving average (STARIMA) and its various extensions. These model specifications assume that the correlation in data can be adequately described by parameters that are globally fixed spatially and/or temporally. They are inadequate for cases in which the correlations among data are dynamic and heterogeneous, such as network data. The aim of this article is to describe autocorrelation in network data with a dynamic spatial weight matrix and a localized STARIMA model that captures the autocorrelation locally (heterogeneity) and dynamically (nonstationarity). The specification is tested with traffic data collected for central London. The result shows that the performance of estimation and prediction is improved compared with standard STARIMA models that are widely used for space–time modeling. En los últimos años, se han propuesto diversas especificaciones de modelado estadístico para describir procesos espacio‐temporales. Esto incluye el modelo espacio‐temporal autorregresivo integrado de media móvil (STARIMA) y sus varios derivados. Estas especificaciones de modelo asumen que la correlación de los datos puede ser adecuadamente descrita por parámetros que se fijan a nivel global en el espacio y/o tiempo. Dichos parámetros son inadecuados para los casos en los que las correlaciones entre los datos son dinámicas y heterogéneas, como en el contexto de los datos de la red. El objetivo de este artículo es describir la autocorrelación en los datos de red con una matriz de ponderación espacial dinámica y un modelo STARIMA localizado (LSTARIMA) que captura la autocorrelación local (heterogeneidad) de forma dinámica (no estacionariedad). La especificación del modelo es evaluada con datos de tráfico recolectados en el centro de Londres. Los resultados demuestran que los rendimientos de estimación y predicción mejoran con el método propuesto en comparación con los modelos STARIMA estándar que son ampliamente utilizados para el modelado de espacio‐temporal. 通过设定多种统计模型来描述地理时空过程已提出多年，包括时空自回归移动平均(STARIMA)及其变形。此类模型通过假设数据相关性可由在时间域或者空间域上全局不变的参数加以充分描述。因此，上述模型不适用于具有动态或异质相关性的数据，如网络数据。本文试图采用一个动态空间权重矩阵与局部时空自回归移动平均(LSTARIMA)模型来描述数据的自相关程度，以此捕捉局域自相关(异质性)和动态自相关(非平稳性)。以伦敦市中心的交通数据作为模型的实证案例的测试结果显示，相对于广泛应用于时空过程分析的标准STARIMA模型，本文的模型在参数估计和预测性能上均有提升。